Numerical seismic assessment of masonry made of compressed earth blocks - Nitiffi, Riccardo (2018)
Masonry construction built with compressed earth blocks (CEBs) is one of the most significant examples of sustainable buildings based on the earth construction technology. Nevertheless, despite the economic and environmental advantages, the seismic vulnerability of these construction is object of concern. The aim of the present paper is to numerically investigate the response of a one-story CEB masonry building subjected to horizontal forces simulating seismic actions. Both modal and non-linear static analyses are performed through the commercial Finite Element (FE) code TNO-DIANA by using a 3D FE macro-modelling approach. During the analyses, particular attention has been devoted to the influence of some structural elements such as interior partition walls and ring beams.